Diabetes, pre-diabetes, and cardiovascular diseases : task force on diabetes and cardiovascular diseases of the European Society of Cardiology (ESC) and of the European Association for the Study of Diabetes (EASD) - Rydén, Lars; Standl, Eberhard (European Society of Cardiology, 2007)
Guidelines that focus on the treatment of diabetes mellitus and related cardiovascular diseases. Intended for professional public.
ESC Pocket Guidelines
Keywords: kardiovaskulární nemoci; Quality Assurance, Health Care; diabetes mellitus; komorbidita; Diabetes Mellitus; Patient Care; zajištění kvality zdravotní péče; Comorbidity; péče o pacienta; Cardiovascular Diseases; Heart Disease Risk Factors; rizikové faktory kardiovaskulárních chorob; kardiologie; diabetologie